1990
DOI: 10.1152/ajpregu.1990.259.1.r84
|View full text |Cite
|
Sign up to set email alerts
|

Effect of converting-enzyme inhibition on renal response to ANF in rats with experimental heart failure

Abstract: Increased activity of the renin-angiotensin system is thought to play a major role in the pathogenesis of salt retention and edema formation in congestive heart failure. The present study evaluates the effects of chronic inhibition of angiotensin-converting enzyme on the response to infusion of exogenous atrial natriuretic factor (ANF) in salt-retaining rats with chronic arteriovenous (a-v) fistula, an experimental model of high-output congestive heart failure. Administration of ANF in incremental doses (5-50 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
40
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 0 publications
2
40
0
Order By: Relevance
“…Importantly, the potentiating action oflow dose inhibition ofAll generation occurred despite a tendency towards reduced renal perfusion pressure, a parameter of profound functional importance for renal responses to ANF (5). Analogously, Abassi et al (17) demonstrated that CEI potentiated natriuretic responses to ANF in CHF despite significant decreases in renal perfusion pressure. Moreover, the observation that chronic inhibition of All generation did not significantly alter systemic hemodynamics at baseline compared with untreated CHF suggests that potentiation of NEP-I action was not simply a consequence of reducing the hemodynamic severity of CHF.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Importantly, the potentiating action oflow dose inhibition ofAll generation occurred despite a tendency towards reduced renal perfusion pressure, a parameter of profound functional importance for renal responses to ANF (5). Analogously, Abassi et al (17) demonstrated that CEI potentiated natriuretic responses to ANF in CHF despite significant decreases in renal perfusion pressure. Moreover, the observation that chronic inhibition of All generation did not significantly alter systemic hemodynamics at baseline compared with untreated CHF suggests that potentiation of NEP-I action was not simply a consequence of reducing the hemodynamic severity of CHF.…”
Section: Discussionmentioning
confidence: 89%
“…Studies by Appel et al (32) demonstrate that ANF, and its intracellular second messenger cGMP, dose-dependently antagonize AII-mediated mesangial cell contraction. In addition, Showalter et al ( 16) observed that low dose intrarenal All attenuates ANF-mediated changes in both GFR and tubular sodium reabsorption in the normal dog, while the studies of Abassi et al (17) indicate that CEI restores tubular responses to ANF in rats with CHF. Studies by Salazar et al (33) suggest that All antagonizes ANF induced decreases in proximal tubule reabsorption.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic inhibition of angiotensin-converting enzyme (ACE), to reduce angiotensin II production, has been shown to improve the natriuretic response to ANP in animal models of cardiac failure (Raya et al, 1989;Abassi et al, 1990;Villarreal et al, 1992). This has prompted interest in the effect of ACE inhibitors on the response to E-24.11 inhibition and the possibility of synthesizing dual inhibitors i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical and experimental data provide strong evidence that this axis is involved in the pathogenesis of the cardiac, renal, and vascular changes of CHF and hypertension (2,4,7,12,14,35,37). Moreover, inhibitors of angiotensin-converting enzyme (ACE) have been found to be highly beneficial in the treatment of patients with CHF (2, 4, 31a, 31b, 37).…”
mentioning
confidence: 99%